Anchors Aweigh. Issue 73 (September 2014) - Tudball, Dan
<x xml:space="preserve">Abstract</x> A new paper from Paul Wilmott, Alan Lewis, and Daniel Duffy makes a rare connection between theories and honest‐to‐goodness practical quantitative finance.